Early experience of stereotactic biopsy of brain lesion in tertiary centre of Nepal - Jha, Binit Kumar; Jha, Prabhat; Jha, Rajiv; Bista, Prakash (Nepal Journal of Neuroscience, 2021)
Background Stereotactic surgery or stereotaxy is a minimally invasive form of surgical intervention which makes use of a three-dimensional coordinate system to locate small targets inside the body and to perform on them some action such as ablation, biopsy, lesion, injection, stimulation, implantation, radiosurgery (SRS), etc. Though it was developed a long time ago as a useful adjunct to brain lesions evaluation, use in Nepal is quite recent. Materials and Methods The study included eight patients who underwent frame based stereotactic biopsy and pathological evaluation of specimen at National Academy of Medical Sciences (NAMS). Results Out of eight patients the results were positive in seven patient and negative in one patient. Conclusions The basic advantages of stereotaxy were realized in our cases with minimal morbidity and no mortality. Craniotomy for biopsy could be avoided.